Reactive arthritis at the Sydney Sexual Health Centre 1992–2012: declining despite increasing chlamydia diagnoses. (September 2016) - Mason, E; Wray, L; Foster, R; Jamil, MS; Guy, R; McNulty, A; Donovan, B
Summary: Reactive arthritis is an under-studied complication of genital Chlamydia trachomatis infection (chlamydia). We assessed trends and risk factors for reactive arthritis in a large urban sexual health clinic. Using a case-control design, data on reactive arthritis cases and controls at the Sydney Sexual Health Centre over the period 1992–2012 were extracted and multivariate analyses were performed. Trend analyses were performed on reactive arthritis diagnoses. Over the 1992–2012 study period, 85 reactive arthritis cases were diagnosed at Sydney Sexual Health Centre. The rate of reactive arthritis diagnoses decreased over time (23 in 1992–1996 to one in 2007–2011 and none in 2012), while chlamydia diagnoses increased (770 in 1992–1996 to 2257 in 2007–2011). In multivariate analysis, factors independently associated with a reactive arthritis diagnosis were: being male (adjusted odds ratio [aOR] 3.27; 95% confidence interval [CI] 1.04–10.32; p = 0.043) or born overseas (aOR 2.69; 95% CI 1.27–5.70; p = 0.010), while a past sexually transmitted infection other than chlamydia or non-gonococcal urethritis was protective (aOR 0.21; 95% CI 0.10–0.45; p < 0.001). Reactive arthritis was not associated with current or recent chlamydia infection ( p = 0.184) but was marginally associated with past non-gonococcal urethritis ( p = 0.080). This study found a decline in reactive arthritis diagnoses despite an increase in chlamydia diagnoses.